ORIGINAL PAPER Erythropoietin therapy in chronic renal failure patients prior to hemodialysis - Rysz, Jacek; Bartnicki, Piotr; A. Stolarek, Robert (Archives of Medical Science, 2005)
The human recombinant erythropoietin (hrEpo) is crucial in anemia treatment options in chronic renal failure patients undergoing regular hemodialysis therapy. However, the clinical characteristics of erythropoietin treatment prior to hemodialysis have not been thoroughly studied. This study was aimed to analyze in retrospective manner the results of hrEpo therapy in chronic renal failure prior to hemodialysis. The study included 42 patients (26 males and 16 females, 42.4±3.7 yrs old) with mean serum creatinine 305±32 µmol/l, whose anemia and iron homeostasis parameters were carefully assessed. HrEpo improved both the general state of the patients and the life quality, it decreased cardiovascular complications and the mortality of patients prior to hemodialysis therapy. Iron supplementation during erythropoietin therapy was required, in the majority of patients oral iron was sufficient. The application of human recombinant erythropoietin prior to hemodialysis is a safe option, it does not accelerate the progression of chronic renal failure, only in a small number of patients moderate increase of blood pressure was noted that could have been effectively managed with the modification of doses of hypotensive pharmacotherapy.